ENHANCING EMPLOYEE PERFORMANCE THROUGH WORK ETHIC AND COMPETENCE: THE MEDIATING ROLE OF WORK ENGAGEMENT - Karesya Rezkia Pasha; Fanlia Prima Jaya; Titien Agustina (International Journal of Multidisciplinary Reseach, 2026)
Employee performance remains a critical issue in public organizations because service quality is closely associated with employees’ ability to perform their responsibilities effectively. This study examined the relationships among work ethic, competence, work engagement, and employee performance. A quantitative cross-sectional approach was employed using a census of 85 employees. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model satisfied the requirements for reliability, convergent validity, and discriminant validity before evaluating the structural model. Work ethic exerted positive and significant effects on both work engagement and employee performance. Competence positively influenced work engagement but did not significantly affect employee performance. Work engagement was not associated with employee performance and did not mediate the relationships between work ethic and employee performance or between competence and employee performance. The proposed model explained 66.8% of the variance in work engagement and 84.8% of the variance in employee performance. Employee performance in the public sector therefore depends more strongly on work ethic than on competence alone, while competence requires appropriate job alignment to contribute more effectively to performance.